On the Marxist Concept of Humanism - Morkūnienė, J. (Problemos, 1978)
The article tries to reveal the distinction between the scientific-theoretical aspect and the value aspect in Marxist humanism on the basis of their pertinence to scientific and routine levels of social consciousness. The fundamental principles of the theory of scientific humanism and their methodological importance are pointed out.